(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to know (the effect of the method of trust and its preservation in the achievement of Arabic grammar for second-grade intermediate students), and to verify the current research, the researcher formulated the following null hypothesis: There are no statistically significant differences at the level of significance (0.05) between the average scores of the experimental group students who studied according to the (see before you hear) method in the collection of Arabic grammar and the average scores of the control group students who studied the same subject in the traditional way collection" And among the students of the second experimental group who studied according to the method of (building and maintaining confidence) in the collection of Arabic grammar, and the average scores of the students of the control group who studied in the traditional way the same subject in achievement.